Poor glycemic control impairs oral health in children with type 1 diabetes mellitus - a systematic review and meta-analysis - Zsuzsanna Triebl; Bulcsú Bencze; Dorottya Bányai; Noémi Rózsa; Péter Hermann; Dániel Végh (BMC, 2024)
Abstract Objective There are more than one million children and adolescents living with type 1 diabetes mellitus, and their number is steadily increasing. Diabetes affects oral health through numerous channels, including hyposalivation, immune suppression, and the inflammatory effect of glycation end-products. However, patients with type 1 diabetes must follow a strict sugar free diet that is proven to be carioprotective. Therefore, the aim of this systematic review and meta-analysis is to investigate whether children with type 1 diabetes have a difference in Decayed, Missing, Filled Teeth index (DMFT), salivary function, and periodontal status than children without diabetes, with an emphasis on glycemic control. Materials and Methods PubMed, Embase and Cochrane libraries were screened for articles, using predefined search keys without any language or date restrictions. Two independent authors performed the selection procedure, extracted data from the eligible articles, carried out a manual search of the reference lists, and assessed the risk of bias using the Newcastle-Ottawa scale. Meta-analysis was performed in R using the random-effects model. Effect sizes were mean differences; subgroup analysis was performed on glycemic control. Results 33 studies satisfied the eligibility criteria. 22 studies did not show a significant difference regarding the DMFT index between the diabetes and non-diabetes groups; six studies found that children living with diabetes had higher DMFT scores, compared to five studies that found significantly lower scores. Meta-analysis found no statistically significant differences in plaque, gingival, and calculus indexes, however it found significant differences in pooled DMFT indexes, and salivary flow rate. Subgroup analysis on glycemic control using DMFT values found significant differences in children with good and poor glycemic control with results of 0.26 (CI95%=-0.50; 1.03) and 1.46 (CI95%=0.57; 2.35), respectively. Conclusions Children with poor glycemic control face higher risk of developing caries compared to good control and non-diabetes children. Regular dental check-ups and strict control of glycemic levels are highly advised for children living with type 1 diabetes, further emphasizing the importance of cooperation between dentists and diabetologists.